"Jest dobrze, będzie jeszcze lepiej". Nowe granice zachodnie Polski w dyskursie publicystyczno-naukowym lat 40. XX wieku = "It`s good, it will be better". The new western borders of Poland in journalistic and academic discourse from the 1940s. - Strauchold, Grzegorz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The fact of obtaining German Eastern territories to the Oder-Neisse line ( including Szczecin), which actually meant the shift of the border almost to Central Germany, unleashed enormous journalistic and research energy. The authors of numerous articles published in periodicals and brochures, and later in authoritative analysis and research monographs, tried to make a Polish reader familiar with the issues connected with the territories newly incorporated into the Polish state.
Keywords: pogranicze polsko-niemieckie; Ziemie Odzyskane; Ziemie Zachodnie; publicystyka; Polska; od 1945 r.